2019
DOI: 10.1128/mbio.00459-19
|View full text |Cite
|
Sign up to set email alerts
|

Dengue and Zika Virus 5′ Untranslated Regions Harbor Internal Ribosomal Entry Site Functions

Abstract: The Flavivirus genus of the Flaviviridae family encompasses numerous enveloped plus-strand RNA viruses. Dengue virus (DENV), a flavivirus, is the leading cause of serious arthropod-borne disease globally. The genomes of DENV, like the genomes of yellow fever virus (YFV), West Nile fever virus (WNV), or Zika virus (ZIKV), control their translation by a 5′-terminal capping group. Three other genera of Flaviviridae are remarkable because their viruses use internal ribosomal entry sites (IRESs) to control translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 42 publications
(60 reference statements)
9
54
0
Order By: Relevance
“…IRES sequences allow cap-independent translation under certain conditions, including cellular stress (reviewed in [28]). IRES sequences were originally identified in viruses [29,30], and since then a number of viruses including DENV and ZIKV have been shown to have functional IRES sequences [31]. However, to date we have been unable to find reports of a functional IRES sequence in JEV.…”
Section: Discussionmentioning
confidence: 95%
“…IRES sequences allow cap-independent translation under certain conditions, including cellular stress (reviewed in [28]). IRES sequences were originally identified in viruses [29,30], and since then a number of viruses including DENV and ZIKV have been shown to have functional IRES sequences [31]. However, to date we have been unable to find reports of a functional IRES sequence in JEV.…”
Section: Discussionmentioning
confidence: 95%
“…This is reminiscent of the uncoupling of translational suppression from cellular stress responses observed during flavivirus infection, with the difference that DENV and ZIKV infection antagonize eIF2α phosphorylation [79]. Since flavivirus and MNV infection results in the activation of the p38-Mnk1 signaling cascade to regulate eIF4E activity, and PABP activity for MNV, and given that both flavivirus and calicivirus translation are driven by cap-independent translation mechanisms, we propose that the suppression of the host translation by targeting the cap-binding complex, rather than through eIF2α activity, could confer a selective advantages to maintain viral translation in conditions where global translation is impaired [37,40,45,79,80]. Noticeably, it has also been reported that some forms of stress lead to a phosphorylation of eIF2α correlating with only moderate translation shut-off and without any SG formation [53,54].…”
Section: Discussionmentioning
confidence: 96%
“…Given the prior connection of RPS25 to IRES-mediated translation events, one interpretation from the potent DENV resistance phenotype of RPS25-deficient cells is that DENV utilizes a specialized translation mechanism despite the presence of a cap on its gRNA (Hafirassou et al, 2017). Such an interpretation may be supported by the observation that DENV translation can operate under cellular conditions where cap-dependent translation is inhibited (Edgil et al, 2006), and the recent suggestion that the DENV and ZIKV 5' untranslated regions harbor certain IRES properties (Song et al, 2019).…”
Section: Rps25 Loss Is Protective Against Flavivirus Infection and Thmentioning
confidence: 99%